Analisis Pemahaman Siswa Sekolah Dasar Tentang Bentuk Dan Perubahan Energi Dalam Kehidupan Sehari-Hari Di SDN 1 Narimbang Mulia - Anisa Nurfadila Ramadhani; Peni Irawati; Siti Fatonah; Yadi Heryadi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research is motivated by the problems faced by fifth-grade students at SDN 1 Narimbang Mulia in understanding the material on forms and changes of energy in everyday life. One of the main obstacles identified is the lack of teaching aids and the unappealing nature of student worksheets, which hampers the learning process. The purpose of this study is to analyze the level of elementary students' understanding of the forms and changes of energy, as well as to identify the obstacles they face in learning the material. This research uses a qualitative approach with data collection techniques including student observations, teacher interviews, and the administration of a post-test at the end of the learning session. The research subjects are fifth-grade students of SDN 1 Narimbang Mulia. The results of the study show that most students have a fairly good understanding of the concepts of energy forms and changes. However, there are still obstacles in the learning process, including limited teaching aids and uninteresting student worksheets. This study is expected to serve as a basis for developing more effective learning strategies to improve students' understanding of the material on energy forms and changes in everyday life.